ChemInform Abstract: Preparation and Regioselective Magnesiation or Lithiation of Bis(trimethylsilyl)methyl‐Substituted Heteroaryls for the Generation of Highly Functionalized Heterocycles. Issue 41 (October 2015) - Klatt, Thomas; Werner, Veronika; Maximova, Marina G.; Didier, Dorian; Apeloig, Yitzhak; Knochel, Paul
Abstract A wide range of bis(trimethylsilyl)methyl (BTSM)‐substituted heteroaryl derivatives is prepared by using Kumada—Corriu or Negishi cross‐coupling reactions.